El Romanç d'Evast e Blaquerna i el concepte missional lul·lià: una aplicació pràctica a l'Amèrica del segle XVI. - PÉREZ CASTAÑEDA, MANEL (Scripta)
The Romanç d'Evast e Blaquerna has often been noted of utopic. In this work we have sought to disprove this idea, linking it to the fact that the missionary ideal that Llull exposes to the Blaquerna took place more than two hundred years after its writing. Thus, one can see the missionary ideal as Llull as a clear reference of Bartolomé de Las Casas' missionary practice in 16th-century America. The study of indigenous languages and cultures and the treatment of equals between missionaries and infidels, which is why it is necessary to use reasons above the use of force, converge on the evangelizing will of both protagonists. Keywords: Llull, Blaquerna, mission, Las Casas, evangelization.